Bison and cattle grazing influences on soil microbial N cycling and ecosystem N pools in annually burned tallgrass prairies - Vega Anguiano, Nicholas (Kansas State University, 2024)
Nitrogen (N) cycling is soil microbially mediated and essential for soil fertility. Grazing animals are integral to N cycling in grassland systems, especially historically grazed grasslands like the tallgrass prairie ecosystem which supported large populations of bison pre-colonization. Grazing animals impact the N cycle by recycling forage through consumption and deposition of more bioavailable N to the soil, promoting soil fertility. However, bison and cattle may have different impacts on N cycling due to differences in management, physiology, and behavior. Further comparative impacts of bison and cattle grazing on N cycling in tallgrass prairie have not been investigated. I predicted that N cycling microbial activities and plant and soil N pools would be similarly higher under both types of grazing relative to ungrazed conditions. To evaluate these predictions, I sampled upland mineral soils in annually burned bison-grazed, cattle-grazed, and ungrazed experimental tallgrass prairie watersheds at the Konza Prairie Biological Station near Manhattan, KS, USA, over the 2020-2022 summer growing seasons; and measured soil characteristics, N availability indices, microbial N cycling activity rate potentials, and N pools including total soil N, soil microbial biomass N, and aboveground primary productivity and forage N uptake within moveable exclosures with paired ungrazed plots. Overall, soil N cycling rates in bison-grazed watersheds were higher than in ungrazed watersheds, and generally intermediate between the two in cattle-grazed watersheds. Under bison, there was higher soil pH, plant available N, lower extracellular enzyme activity estimated N limitation, and greater nitrification and denitrification potential than in ungrazed soils, though effects on denitrification were weaker than on N mineralization and nitrification. Forage N content, soil N concentration and N stock was also higher under bison grazing than in cattle grazed or ungrazed conditions. Interannual variability in microbial N cycling was high, and likely related to higher precipitation and soil moisture in 2020 than 2021 and 2022 but did not change grazing effects. However, dung N content did not differ between the two grazers, and forage production and N uptake into grass was significantly greater under cattle than bison grazing. In conclusion, while ungrazed soils had lower N-cycling rates and higher C:N ratios than either bison or cattle grazed soils, both soil fertility and forage quality was consistently greater under bison than cattle grazing. Results show that higher grass %N under bison grazing is related to more plant available N, accelerated soil N cycling rates, and a larger soil N stock, showing that stronger grazer-plant-soil fertility feedbacks exist in bison-grazed prairie than cattle-grazed prairie. Differences may be attributed either to animal physiology and behavior, and/or to greater grazing pressure from bison than cattle due to different management. This investigation establishes that relationships between animal and soil microbial processes mediate terrestrial N cycling in tallgrass prairie, and may be used to inform cattle and bison rangeland management decisions.
Keywords: Tallgrass prairie; Nitrogen cycle; N budget; Soil microbial activities; Bison and cattle grazing; Grazing lawns